Stable tetrabenzo-chichibabin’s hydrocarbons : tunable ground state and unusual transition between their closed-shell and open-shell resonance forms - Zeng, Zebing (2013)
Stable open-shell polycyclic aromatic hydrocarbons (PAHs) are of fundamental interest due to their unique electronic, optical, and magnetic properties and promising applications in materials sciences. Chichibabin’s hydrocarbon as a classical open-shell PAH has been investigated for a long time. However, most of the studies are complicated by their inherent high reactivity. In this work, two new stable benzannulated Chichibabin’s hydrocarbons 1-CS and 2-OS were prepared, and their electronic structure and geometry in the ground state were studied by various experiments (steady-state and transient absorption spectra, NMR, electron spin resonance (ESR), superconducting quantum interference device (SQUID), FT Raman, X-ray crystallographic etc.) and density function theory (DFT) calculations. 1-CS and 2-OS exhibited tunable ground states, with a closed-shell quinoidal structure for 1-CS and an open-shell biradical form for 2-OS. Their corresponding excited-state forms 1-OS and 2-CS were also chemically approached and showed different decay processes. The biradical 1-OS displayed an unusually slow decay to the ground state (1-CS) due to a large energy barrier (95 ± 2.5 kJ/mol) arising from severe steric hindrance during the transition from an orthogonal biradical form to a butterfly-like quinoidal form. The quick transition from the quinoidal 2-CS (excited state) to the orthogonal biradicaloid 2-OS (ground state) happened during the attempted synthesis of 2-CS. Compounds 1-CS and 2-OS can be oxidized into stable dications by FeCl3 and/or concentrated H2SO4. The open-shell 2-OS also exhibited a large two-photon absorption (TPA) cross section (760 GM at 1200 nm).